Invasive pulmonary aspergillosis in heart transplant recipients: Is mortality decreasing? - Eduardo Flores-Umanzor (Revista Portuguesa de Cardiologia (English Edition), 2021)
Introduction: Infection remains a major complication among heart transplant (HT) recipients, causing approximately 20% of deaths in the first year after transplantation. In this population, Aspergillus species can have various clinical presentations including invasive pulmonary aspergillosis (IPA), which has high mortality (53-78%). Aims: To establish the characteristics of IPA infection in HT recipients and their outcomes in our setting. Methods: Of 328 heart transplantations performed in our center between 1998 and 2016, five cases of IPA were identified. Patient medical records were examined and clinical variables were extracted. Results: All cases were male, with a mean age of 62 years. The most common indication for HT was nonischemic dilated cardiomyopathy. Productive cough was reported as the main symptom. The imaging assessment was based on chest radiography and chest computed tomography. The most commonly reported radiological abnormality was multiple nodular opacities in both techniques. Bronchoscopy was performed in all patients and A. fumigatus was isolated in four cases on BAL culture. Treatment included amphotericin in four patients, subsequently changed to voriconazole in three patients, and posaconazole in one patient, with total treatment lasting an average of 12 months. Neutropenia was found in only one patient, renal failure was observed in two patients, and concurrent cytomegalovirus infection occurred in three patients. All patients survived after a mean follow-up of 18 months. Conclusions: IPA is a potentially lethal complication after HT. An early diagnosis and prompt initiation of aggressive treatment are the cornerstone for better survival. Resumo: Introdução: A infeção continua a ser a principal complicação dos doentes submetidos a transplante cardíaco (TC), originando aproximadamente 20% de mortalidade no primeiro ano pós transplante. Nesta população, a infeção Aspergillus pode causar diferentes quadros clínicos, incluindo a aspergilose pulmonar invasiva (API), com elevada mortalidade (53 a 78%). Objetivos: Estabelecer as características da infeção por API nos doentes de TC e apresentar os respetivos resultados do nosso centro. Métodos: De 328 transplantes cardíacos realizados no nosso centro entre 1998 e 2016, identificámos cinco casos de API. Os registos médicos dos doentes foram examinados e as variáveis clínicas foram analisadas Resultados: Todos os casos corresponderam a doentes do sexo masculino com a idade média de 62 anos. A indicação mais comum para TC foi a miocardiopatia dilatada não isquémica. A tosse produtiva foi registada como principal sintoma. A avaliação radiológica baseou-se na radiografia e na tomografia computorizada ao tórax. A alteração radiológica mais comum foi, em ambas as técnicas, o registo de densidades nodulares múltiplas. A broncoscopia foi realizada em todos os doentes e o aspergillus fumigatus foi isolado em quarto casos de cultura BAL. O tratamento incluiu anfotericina em quatro doentes com mudança subsequente para voriconazol em três doentes e posaconazol em um doente, duração média do tratamento total de 12 meses. A neutropenia foi observada apenas num doente, a insuficiência renal em dois doentes e a infeção por CMV concomitante ocorreu em três doentes. Todos os doentes sobreviveram após um seguimento médio até 18 meses. Conclusões: A API representa uma complicação potencialmente letal após TC. O diagnóstico precoce e a instituição também precoce de tratamento agressivo constituem a pedra angular para uma melhor sobrevivência.